How opportune is multigene testing in metastatic colorectal cancer? A review - Cristina Orlov-Slavu; Andreea Parosanu; Mihaela Olaru; Dragos Serban; Ioana Paunica; Cornelia Nitipir (Journal of Mind and Medical Sciences)
Personalized treatment in oncology is the most innovative method of care. The best method to establish personalized treatment is by genetic characterization of the malignant cell. Theoretically, the more detailed the characterization, the more effective the choice of treatment becomes. Currently, there are fast and relatively low-cost options that allow such genetic characterization. However, test results sometimes do not detect targetable alterations and, even if they do detect, the use of the treatment-alteration combination does not always generate a satisfactory oncological response. The present paper aims to answer two questions. First, how targetable can the most common gene alterations in colorectal cancer be. Second, whether it makes sense to use broad molecular testing as a standard in all metastatic patients.